Factors affecting Changing Gender roles among farm families in Osun State, Nigeria - Jubreel, Olasunbo Kafilat; Ogunleye, Kehinde Yewande; Ayoade, Adenike Rebecca; Adeomi, Damilola Toluse (PT. Riset Press International, 2024)
Gender roles are assumptions that individuals, and the general public have of people based on their biological characteristics. These assumptions are usually as a result of values and beliefs of the society. In spite of the global war against gender inequalities, many societies in Africa are structured in a way that socio-cultural norms form the basis of gender roles. This reflects on many households where men are typically favoured than women in gender roles. However, changing trends across the world has impacted on many areas of society. Therefore, the study assessed the key factors influencing changing gender roles among farm families in Osun State, Nigeria. Data were collected through interview schedule. Multi-stage sampling technique was used to select twenty (20) rural farming households from eight Local Government Areas in the State. Data were described and analyzed using percentage, mean and Pearson product moment correlation. Findings revealed a mean age of 43.5 ± 11.73 years. The mean household size was 6.9±1.7 persons. Access to education and resources (p =0.001) and economic opportunities (p = 0.002). Likewise, environmental factors generally had significant influence on changing gender roles (p = 0.01). This study points to the importance of ensuring that the fair share of responsibilities with regards to gender roles in society is constantly promoted and highlights of their contributions is well recognized.